Youtube Youtube Media As A Means Of Acquisition Arabic For Adolescent Children In Karyamulya Village, Cirebon City: Media Youtube Sebagai Sarana Akuisisi Bahasa Arab Untuk Anak Remaja Di Desa Karyamulya, Kota Cirebon - Fadhil Muhamad pratama; septi gumiandari (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Overview Puberty is a time of self-discovery and they always want to learn new things. All of this is supported by increasingly sophisticated technology and many accessible applications that help you gain new knowledge, such as YouTube videos from your website. This study aims to help level B2 children enter puberty through the media YouTube. This study uses a qualitative and descriptive method. The results of the survey are that Arabic teachers consider the results of this survey when teenagers around the village of Karyamulya in the Cirebon Regency Data obtained from phenomena occurring in the field can be used in the form of conversation results between the speaking partner and the speaking partner. Data were obtained from a case study of a teenager living near the researcher's residence with conditions such as entering adolescence, owning a smartphone, and using YouTube as a learning tool and entertainment.